A perseguição inquisitorial e o criptojudaísmo : estudo dos processos envolvendo o sargento-mor Diogo Vaz e seus familiares (1662-1673) - Góes, Priscilla da Silva (2017)
The present dissertation, entitled "Inquisitorial persecution and Crypto-Judaism: A study of the processes involving the sergeant-general Diogo Vaz and his relatives (1662-1673)", has as a research object the description and analysis of the Inquisition, specifically in the persecution of New Christians accused of Judaizers in the Iberian Peninsula, as well as in the Colony. We sought to investigate the cases of Diogo Vaz Penalvo, his sister Anna Rodrigues and other members of his family. For this, we are based on the categories of the Ginzburg (2001) index of the microhistory studied by Giovanni Levi (1992) and Ginzburg (2006), the category of pariah explained by Weber (2010) and the sociology of secrecy, of Simmel (2009), of fundamental importance for the maintenance of Crypto-Judaism. From this, we follow the following steps: to reconstruct the steps of members of a family arrested by the Holy Office and compare them with other cases already studied, collaborating with the study of religious practices that resisted Catholicism in the colonial period; to find in the reports of the documents indications of religious practices considered deviant from the Catholic faith. Finally, this research aims to contribute to the study of the inquisition with a focus on the persecution of the Crypto-Jews, in an attempt to know the religious practices of a family that suffered for more than a decade humiliation, exile and fire.